Biodiversity of the Sierra del Divisor Zone Reserved (Peru): a view from small mammals - Medina, César E. (2015)
This study documents the small mammalian diversity in the Zona Reservada Sierra del Divisor (ZRSD). Six sites were evaluated between 2011 and 2013 with capture techniques (Victor snap traps, Tomahawk traps, Pitfall traps and mist nets). 67 species of small mammals were recorded (five marsupials, 10 rodents and 52 bats), 32 of which are new records for the ZRSD and two are species of the most rare and endemic rodents of Peru, the “Peruvian Aquatic Rat” Neusticomys peruviensis (Cricetidae: Ichthyomyini) and “Ucayali´s Aquatic Mouse” Amphinectomys savamis (Cricetidae: Oryzomyini). On the other hand, the marsupial Marmosops bishopi; rodents Neacomys minutus, Euryoryzomys macconnelli, Scolomys melanops and Proechimys kulinae; and the bats Artibeus planirostris and Rhinophylla pumilio were the most plenty. Our finding showed the importance of the re-categorization of Reserved Zone to National Park like as a significant contribution to the conservation of the Peruvian mammals.